Effect of Agility Training Method and Leg Muscle Flexibility on Mawashi-Geri Kick Results at Club Karate Bukit Sejahtera, Palembang - Nursamedy, Aris; Pramono, Harry; Sulaiman, Sulaiman (Journal of Physical Education and Sports, 2019)
The purpose of this study is: (1) Analyzing the difference in influence between Illinois agility training methods and t-drill exercises on the results of the Mawashi-Geri kick, (2) Analyzing the effect of high and low leg muscle flexibility category on the results of the Mawashi-Geri kick, (3) Analyze the interaction between the agility training method and leg muscle flexibility on the Mawashi-Geri kick. This study used an experimental method using factorial 2x2 design. The data analysis technique used Variant Analysis (ANOVA) at a significance level (ÃŽÂ±) of 0.05. The subjects in this study were karate athletes at Bukit Sejahtera, Palembang, South Sumatra. The results of this study: (1) There is a difference in influence between Illinois agility training and t-drill on the Mawashi-Geri kick, (2) There is a difference in influence between karate athletes who have the high and low category of leg muscle flexibility on Mawashi-Geri kick, (3) There is an interaction between the agility training method, and leg muscle flexibility towards the Mawashi-Geri kick results at Bukit Sejahtera karate club/dojo, Palembang. Suggestion: sports coaches can use the Illinois agility training method as an alternative training method for the Mawashi-Geri Jodan kick training, and for other researchers who wish to conduct similar research, it is hoped that it will further develop research with a broader scope.